Estrategias y dispositivos comunitarios en procesos de desarrollo territorial en Aldea Beleiro; Chubut, Argentina. - Diez Tetamanti, Juan Manuel (Universidad Nacional del Litoral, 2021)
Aldea Beleiro is one of the three focus localities of research between 2018-2019, with the PICT “Strategies and community and state devices in territorial development processes of small towns and dispersed rural areas in the southwest of the province of Chubut.” The objective is to analyze strategies and devices, both state and community, which, depending on the isolation and integration scenarios, contribute to processes of territorial development in small towns and dispersed rural spaces in the southwest of the province of Chubut. The methodology is approached from the research cartographic and articulates a series of developing and experimental tools. The research process puts in permanent dialogue the texts produced, the partial conclusions and the ideas produced with the local population to think about the different strategies and devices implemented from the community, thus activating micro-processes of territorial development.